2022
DOI: 10.3390/suschem3020014
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity of a Global Binding Framework for Sustainable Management of Chemicals and Materials—Interactions with Climate and Biodiversity

Abstract: Sustainable chemicals and materials management deals with both the risks and the opportunities of chemicals and products. It is not only focused on hazards and risks of chemicals for human health and the environment but also includes the management of material flows from extraction of raw materials up to waste. It becomes apparent meanwhile that the ever-growing material streams endanger the Earth system. According to a recent publication of Persson et al., the planetary boundaries for chemicals and plastics h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…PFAS contribute to this overload and contradict sustainability criteria. Thus, they require stringent global regulation [375].…”
Section: Discussionmentioning
confidence: 99%
“…PFAS contribute to this overload and contradict sustainability criteria. Thus, they require stringent global regulation [375].…”
Section: Discussionmentioning
confidence: 99%
“…As extreme weather events occur more frequently, pollutants are also remobilized through runoff from agricultural fields with pesticide-contaminated topsoil and river sediments during flooding. 44 Exposure to organisms containing these bioactive compounds will harm biodiversity and encourage pesticide resistance. 45…”
Section: Soil Carbon Cyclementioning
confidence: 99%
“…The warming climate, elevated atmospheric CO 2 levels, and nitrogen deposition have boosted gross primary productivity, encouraging vegetation growth and increasing nutrient demand. 44 Though the effect of warming on phosphorus cycling remains a subject of debate, it is widely accepted that the current phosphorus supply may not be sufficient to meet the escalating demands of plants. 145 Research showed that an acidogenic outlet rich in short-chain (volatile) fatty acids can be utilized as a soil amendment which functions as a phosphate solubilizing agent.…”
Section: Cover Cropsmentioning
confidence: 99%
“…Figure 1 below: Each of the construction phases could potentially generate waste. Waste is the excessive consumption of resources and materials: the resources mean human effort, energy, air, water, land and biodiversity (Cobra et al, 2015;Steinh€ auser et al, 2022). This study draws on research conducted in an organisational resource waste management context.…”
Section: Construction Waste and Their Connectivitymentioning
confidence: 99%